Pengaruh Pendekatan Pembelajaran Realistic Mathematics Education (RME) terhadap Kemampuan Pemecahan Masalah dan Berpikir Kritis Matematika Siswa Kelas III SDN 104202 Bandar Setia - Eva Nur Handayani; Zulvia Misykah; Nur Wahyuni; Dinda Widyastika (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This paper seeks to analyze the impact of the Realistic Mathematics Education (RME) approach learning approach on the development of critical thinking and problem-solving skills in third-grade pupils at SDN 104202 Bandar Setia. This research employed a quantitative method with a nonrandomized pretest-posttest control group design, involving two groups: the control group (III A) without treatment and the experimental group (III B) that received the RME learning approach, with a total sample of 50 students. Both groups were administered pre-test and post-test instruments to measure problem-solving and critical thinking skills. The findings revealed that the application of the RME learning approach significantly improved both skills with p < 0.05. These results confirm that RME is effective in enhancing mathematics learning quality through real-life contexts and students’ direct experiences. The implication highlights the importance of integrating RME in elementary mathematics learning as an alternative strategy to foster critical thinking and problem-solving abilities, as well as providing a reference for future instructional innovations.